The use of differential scanning fluorimetry in the rational design of plastic antibodies for protein targets - Ashley, J.; Shukor, Yunus; Tothill, Ibtisam E. (Royal Society of Chemistry, 2016)
The development of molecularly imprinted polymer nanoparticles (MIP-NPs), which specifically bind biomolecules, is of great interest in the area of biosensors, sample purification, therapeutic agents and biotechnology. Polymerisation techniques such as precipitation polymerisation, solid phase synthesis and core shell surface imprinting have allowed for significant improvements to be made in developing MIP-NPs which specifically recognise proteins. However, the development of MIP-NPs for protein templates (targets) still require lengthy optimisation and characterisation using different ratios of monomers in order to control their size, binding affinity and specificity. In this work we successfully demonstrated that differential scanning fluorimetry (DSF) can be used to rapidly determine the optimum imprinting conditions and monomer composition required for MIP-NP design and polymerisation. This is based on the stability of the protein template and shift in apparent melting points (Tm) upon interaction with different functional acrylic monomers. The method allows for the characterisation of molecularly imprinted nanoparticles (MIP-NPs) due to the observed differences in melting point profiles between, protein-MIP-NPs complexes, pre-polymerisation mixtures and non-imprinted nanoparticles (NIP-NPs) without the need for prior purification. The technique is simple, rapid and can be carried out on most quantitative polymerase chain reaction (qPCR) thermal cyclers which have the required filters for SYPRO© orange and could lead to the rapid development of MIPs nanoparticles for proteins.